FEEDING GUIDELINES FOR INFANTS AND TODDLERS (START HEALTHY PROGRAM) - Nancy Butte; Kathleen Cobb; Joanna Dwyer; Laura Graney; William Heird; Caryl Richard ("Paediatrician" Publishers LLC, 2007)
The dietary guidelines for americans contains recommendations on diets and healthy lifestyles but it does not deal with specificities of the diet and feeding breast and small infants (to 2 years). However, parents and carecgivers need practical recommendations on feeding infants and toddlers that are necessary to ensure a normal growth and to create the basis for forming healthy food habits, which apart from other benefits might help prevent the development of obesity and other diseases in both childhood and adulthood. The feeding guidelines for infants and toddlers is aimed at providing parents and carecgivers with practical information on feeding breast and small infants. It is intendced for adding and broadening recommendations worked out by other expert groups and organizations. The article provides a substantiation of the guidelines. The methodology, results and a complete reference list used to work out the recommendations are presented in another document. Key words: infants, nutrition.